Development of a Valid and Reliable Summative Test in Plane Trigonometry - Tandas, Joseph Balinag (Journal of Science and Mathematics Letters, 2021)
The study was carried out to develop a valid and reliable test in Plane Trigonometry for college students. Four research questions were drawn to guide the establishment of validity and reliability for the Plane Trigonometry summative test. It is a multiple choice objective test of four options with 50 items. All students enrolled in plane trigonometry were used as participants to determine the reliability of the test. Three (3) experts/judges were used for the content validity of the test. After validation to the three experts/judges, the result showed that the Plane Trigonometry test has a very high validity. The test item validity was determined through difficulty and discrimination indices. The test has a reliability coefficient of 0.909 established through the use of Cronbach’s Alpha. The test is valid and reliable for assessing students’ content knowledge in Plane Trigonometry. Thus, the constructed test can be used for institutional entrance examination in the field of mathematics education.